Musculoskeletal pain among brazilian textile workers and its relationship with work shifts - Letícia de Lima Trindade; Marjorie Cristine Callai Schuh; Carlise Krein; Lucimare Ferraz; Simone Coelho Amestoy (Universidade Federal de Santa Maria, 2012)
Objective: to better understand the profile of workers who present complaints of musculoskeletal pain in the textile industry in Southern Brazil, as well as to relate the frequency of this symptom with work shifts. Method: the sample was composed of 192 employees in the production sector of a textile manufacturer located in Southern Brazil. Data was collected through the application of a questionnaire with socio-demographic questions and the Nordic Musculoskeletal Questionnaire. Data was analyzed utilizing descriptive statistics and the resources in the Statistical Package for the Social Sciences software. Results: one observes the association between dorsal pain and work shifts (p= 0.007), with greater frequencies among the rotating shift employees. Conclusion: there is a high prevalence of musculoskeletal pain among these workers. The work shift and work dynamics are the principle factors which favor the appearance of musculoskeletal symptoms and that require rapid intervention